Increasing access to care for trauma‐exposed rural veterans: A mixed methods outcome evaluation of a web‐based skills training program with telehealth‐delivered coaching. Issue 4 (14th October 2021) - Fletcher, Terri L.; Amspoker, Amber B.; Wassef, Miryam; Hogan, Julianna B.; Helm, Ashley; Jackson, Christie; Jacobs, Adam; Shammet, Rayan; Speicher, Sarah; Lindsay, Jan A.; Cloitre, Marylène
Abstract: Purpose: While rural veterans with trauma exposure report high rates of posttraumatic stress disorder (PTSD), depression, and functional impairment, utilization of health services is low. This pilot study used mixed qualitative and quantitative methods to evaluate the potential benefits of a transdiagnostic web‐based skills training program paired with telehealth‐delivered coaching to address a range of symptoms and functional difficulties. The study directed substantial outreach efforts to women veterans who had experienced military sexual trauma given their growing representation in the Veterans Healthcare Administration (VHA) and identified need for services. Methods: Participants were 32 trauma‐exposed veterans enrolled in rural‐serving VHA facilities who screened positive for either PTSD or depression. Symptoms of PTSD, depression, emotion regulation, and interpersonal problems were assessed at baseline, midpoint, posttreatment, and 3‐month follow‐up. Veterans completed exit interviews to identify benefits and limitations of the program. Results: Intent‐to‐treat analyses revealed significant symptom reduction for all outcomes, with large to moderate effect sizes at 3‐month follow‐up. Outcomes did not differ by gender or military sexual trauma status. Veterans' rating of the therapeutic alliance was high and interview responses indicated that the presence of the coach was critical to success in the program. Conclusion: This remotely delivered transdiagnostic intervention provided significant benefits across a range of symptoms and functional outcomes and was viewed positively by veterans. The results indicate that further research (ie, a randomized controlled trial) is warranted. Attention to the role of the coach as a means by which to increase engagement and retention in technology‐delivered interventions is warranted.